1963
DOI: 10.1182/blood.v21.5.605.605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Local Irradiation (Co60 Teletherapy) on the Peripheral Blood and Bone Marrow

Abstract: 1. Local Co60 teletherapy caused a reduction in leukocytes and lymphocytes in the peripheral blood. 2. The bone marrow demonstrated no morphologic change in nonirradiated control sites. 3. Local irradiation produced a pronounced and persistent hypoplasia in the treated sites during and after irradiation, with a great reduction in the numbers of megakaryocytes and precursors of red and white cells. During the period of greatest radiation effect the persistent cells were chiefly pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1971
1971
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It is an accepted fact that the hemopoietic system is sensitive to radiation. A pronounced and persistently hypoplastic marrow is produced in the locally irradiated site (6). Also, there is a reduction in the leukocytes and lymphocytes with generally a small amount of change in the red cell and platelet values in the peripheral blood after local irradiation (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an accepted fact that the hemopoietic system is sensitive to radiation. A pronounced and persistently hypoplastic marrow is produced in the locally irradiated site (6). Also, there is a reduction in the leukocytes and lymphocytes with generally a small amount of change in the red cell and platelet values in the peripheral blood after local irradiation (6).…”
Section: Discussionmentioning
confidence: 99%
“…A pronounced and persistently hypoplastic marrow is produced in the locally irradiated site (6). Also, there is a reduction in the leukocytes and lymphocytes with generally a small amount of change in the red cell and platelet values in the peripheral blood after local irradiation (6). The possible explanation for the observed leucopenia is that during a course of fractionated radiotherapy, a large number of circulating stem cells enter the irradiated site and are destroyed, creating a leukocyte depression (7).…”
Section: Discussionmentioning
confidence: 99%
“…Total body irradiation has been linked to bone marrow suppression [ 71 , 72 ], spurring the development of focal RT regimens to reduce hematologic toxicity [ 73 ]. Focal irradiation with limited bone marrow involvement appears to have mild effects on circulating white blood cells, and local areas of bone marrow injury can regenerate with time [ 74 , 75 ]. Local RT has also been shown to recruit bone marrow precursors to the irradiated site [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that external beam RT for tumors of various primary sites is associated with a 24–37% decrease in WBC counts by the end of treatment [4, 5, 7, 8, 2325]. Baseline WBC counts have been found to be highly predictive of leukopenia during RT for various solid malignancies [3, 8, 9].…”
Section: Discussionmentioning
confidence: 99%